Assessment of the adaptive reserve in children with sarcopenia based on the activity level of regulatory systems - O.S. Palamarchuk; K.Yu. Petrik; O.A. Rishko; M.I. Nemesh; O.P. Krichfalushii; S.V. Patskun; O.M. Horlenko (Zdorovʹe Rebenka)
Background. Sarcopenia, commonly linked with aging, has recently been observed in children, affecting 5–40 % of the pediatric population. Loss of muscle mass in childhood limits physical performance and increases the risk of injuries and metabolic disorders, potentially leading to long-term health complications. The purpose of this study was to assess the level of adaptive reserves in children with sarcopenia using the indicator of regulatory systems activity (IRSA) compared to children of the same age and sex without signs of sarcopenia, as well as to establish the relationship of IRSA with body composition and muscle strength. Materials and methods. The study was conducted on a sample of 112 children aged 10–14 years. Muscle mass and strength were assessed via bioelectrical impedance and grip test, respectively. Heart rate variability analysis was used to evaluate cardiovascular system reserves and adaptive potential. Results. The grip strength (GS) of children with sarcopenia was significantly lower than in the control group: by 26.9 % in girls and by 28.7 % in boys (p < 0.01). Sarcopenia index (SI) and body fat (BF) percentage differed markedly, with SI in the main group being 27.2 and 28.5 % lower in girls and boys, respectively (p < 0.05), and BF being 19.8 % higher in sarcopenic girls (p < 0.01). Furthermore, IRSA values were significantly higher in children with sarcopenia: by 47.5 % in girls and by 56.3 % in boys, indicating reduced adaptive capacity (p < 0.01). Correlation analysis revealed a negative relationship between IRSA and both SI and GS among sarcopenic children, along with a positive correlation between IRSA and BF percentage in girls. These findings suggest a relationship between body composition and children’s adaptive reserves, assessed based on heart rate variability. Conclusions. In patients with sarcopenia, IRSA significantly exceeds the values observed in children without sarcopenia, indicating a decrease in adaptive reserve. A negative correlation between IRSA and muscle mass components (SI and GS) has been identified, confirming the impact of muscle mass deficiency on adaptive reserve.